Guided Endodontic Treatment of Mandibular Incisor with Pulp Canal Obliteration following Dental Trauma: A Case Report - Valverde Haro, Henry Paul; Quille Punina , Luis Gustavo; Erazo Conde , Adriana Denisse (Iranian Endodontic Journal, 2024)
Root canal obliteration is caused by hard tissue apposition and is often associated with teeth with a history of trauma, orthodontic movement, caries reaction, restorative procedures near the pulp chamber, and teeth of elderly patients. Preoperative planning of root canal treatment should be thorough and include an assessment of the patient's signs and symptoms in addition to the evaluation of complementary examinations. In a 27-year-old patient with dyschromia of the lower central incisor, a history of dental trauma, and a positive response to vertical percussion, an initial periapical radiograph was obtained that showed calcification of the canal and presence of a periapical lesion. The patient presented with pain on chewing, a positive response to palpation and a vertical percussion test. The diagnosis was symptomatic apical periodontitis. A cone-beam computed tomography scan was requested and a surface scan was performed to establish a static guide. The root canal was accessed in the middle third of the root and the canal was located using a minimally invasive approach. The root canal was treated conventionally. Results obtained showed the success of the treatment after a 3-year clinical and radiographic follow-up. Therefore, the use of an endodontic guide in cases of calcified canals significantly reduces the clinician's working time and offers a more predictable approach to the treatment of these pathologies.